The prevalence and its associated factors of psychological stress among middle school students in China: pooled evidence from a systematic scoping review - Hao, Li; Mat Ludin, Arimi Fitri; Ahmad, Mahadir; Meng, Xie; Zhong Lei, He (Frontiers in Public Health, 2024)
Psychological issues are of significant concern in present-day society, as poor mental well-being results in depression and suicidal behavior. Understanding the current situation of psychological stress among secondary school students will help policy makers to formulate targeted measures to help them cope with stress, and at the same time evaluate the effectiveness of the existing policies to address the shortcomings and enhance the diversification of interventions. The main purpose of this review was to map the existing evidence on the prevalence and levels of psychological stress among adolescents in China, and to identify the associated risk factors. This review strictly adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). A comprehensive search was performed spanning Web of Science, PubMed, and Scopus databases. Studies involving only humans and full text in English were selected. Selection was limited to samples from mainland China, Hong Kong, Macau, and Taiwan. Variables were extracted, exploring the factors that affected the mental wellness of Chinese middle school students. A final 15 articles and 1 report were included. The findings revealed psychological stress is prevalent among Chinese middle school population, with the degree of prevalence from low to severe stress levels. Three dimensions of psychological stress affecting Chinese secondary school students: school, family and lifestyle. Within the school, the factors included academic stress, peer relationships etc. Family-related factors were comprised of parent-child relationship, parents’ mental health status etc. Lastly, lifestyle-related factors included poor diet, sedentary and inactivity etc. Our findings suggest that policy makers should reduce the excessive emphasis on examination results and focus on the all-round development of students, and that schools should organize a variety of extra-curricular activities to reduce students’ stress. Parents should create a harmonious family atmosphere to minimize conflicts and maintain close communication with teachers. Systematic Review Registration OSF; https://doi.org/10.17605/OSF.IO/HEFCP.